Discovery of a novel binding pocket in PPARγ for partial agonists: structure-based virtual screening identifies ginsenoside Rg5 as a partial agonist promoting beige adipogenesis - Zhen Wang; Kexin Shui; Zehui Zhang; Yihan Chen; Nanfei Yang; Shiliang Ji; Pingping Shen; Qiang Tian; Qiang Tian (Frontiers in Chemistry)
Peroxisome proliferator-activated receptor gamma (PPARγ) is a key target for metabolic disorders that contribute to obesity and type 2 diabetes mellitus (T2DM). However, full agonists such as thiazolidinediones (TZDs) have limitations in terms of side effects. Selective PPARγ modulators (SPPARγMs) that target alternative binding pockets offer the potential for safer partial agonists. Here, we employed six computational algorithms (Fpocket, DeepSite, CavityPlus, DoGSiteScorer, CASTpFold, POCASA) to identify a novel allosteric pocket (pocket 6–5) in the PPARγ ligand-binding domain (LBD), localized at the helix 3 (H3), helix 2 (H2), helix 2'(H2′), and β-sheet interface. A virtual screening of 4,097 natural compounds from traditional Chinese medicine (TCM) libraries was conducted, which led to the identification of ginsenoside Rg5 (TWSZ-5) as a top hit. Molecular docking and molecular dynamics (MD) dynamics revealed TWSZ-5 stabilizes pocket 6–5 through hydrogen bonds with Ser342, Gln345, Lys261, and Lys263. TWSZ-5 promoted beige adipocyte differentiation in adipose-derived stem cells (ADSCs) in vitro, upregulating Ucp1, Prdm16, Cpt1α, and Pgc1α. The present study identifies TWSZ-5 as a novel SPPARγM that utilizes an allosteric binding pocket to enhance thermogenesis while mitigating adverse effects. These findings emphasize the potential of TCM derivatives and structure-based screening strategies to develop safer antidiabetic therapies with precision pharmacology.